Alain Badiou and Marcel Gauchet, What Is To Be Done? A Dialogue on Communism, Capitalism, and the Future of Democracy (Malden, MA: Polity Press, 2016) - Giorgio Baruchello (The University of Akureyri, 2018)
A review of the book: Brendan Myers, Reclaiming Civilization: A case for optimism for the future of humanity. A Study of the Sacred, Part Three (Gatineau: Northwest Passage Books, 2016)